Efektivitas Ekstrak Kulit Rambutan (Nephelium lappaceum) Terhadap Penurunan Kadar Low Density Lipoprotein - Nindhea Ferliza, Yoan; Katarina, Shinta; Dody Wibowo, Aldinol; Farida Muhajir, Nurlaili; Arisandi, Desto (Jurnal Medisains Kesehatan, 2024)
Dyslipidemia is a lipid component disorder characterized by increased levels of total cholesterol, Low-Density Lipoprotein (LDL), and triglycerides, as well as decreased levels of High-Density Lipoprotein (HDL). Rambutan is known to contain flavonoids, tannins, saponins, quercetin and alkaloids, which have the ability to lower blood cholesterol levels. The aim of the research was to determine the effect of giving rambutan peel extract to rats on reducing low density lipoprotein (LDL) cholesterol levels. This is a true experiment research with a pretest-posttest and control group design approach.  The research samples were 15 male rats aged 8-10 weeks and weighing 150-250 grams. The dose of rambutan fruit peel was given at 180 mg/kgBW/day for 14 days. LDL cholesterol levels were measured by a spectrophotometer using an enzymatic method. Data analysis used the paired t-test on STATA for Windows software version 12.0 with a confidence level of 95%. Average LDL cholesterol levels in rats before and after administration were 53 and 35 mg/dl, respectively. Giving rambutan skin extract at a dose of 180 mg/dl can reduce LDL cholesterol levels significantly (p < 0.001) by 18 mg/dl (33.9%) in rats